A window of opportunities: Composing a relational space for living and telling sustainable stories to live by - Mette Bøe Lyngstad; Bodil H. Blix (Nordic Journal of Art and Research, 2023)
This article is based on experiences with the Dreamcatchers, a project involving people living with substance addiction, and their significant others, in which the participants composed and explored narratives through creative, collaborative processes. In the article, we think with a narrative composed by one of the participants in the project to learn from her experiences. Our thinking is inspired by narrative inquiry as a way of thinking about experience. We understand the playful and imaginative narrative processes within the Dreamcatchers project as composing sustainable stories to live by. The Dreamcatchers project demonstrates the necessity of involving people living with substance addiction in naming the problem and in the search for possible and sustainable solutions or improvements.